ANALISIS ENERGI DAN EKSERGI PENGERING PAKAIAN SISTEM POMPA KALOR - Indra Hermawan (LPPM Politeknik LP3I Medan, 2018)
Heat pump is a tool that can be used as a dryer, which has the potential as an energy-efficient dryer. This study aims to analyze energy and exergy in the process of drying clothes by using a heat pump system with polyester clothing material. The results showed that the drying rate in the process of drying clothes using a heat pump system with polyester clothing material was 1.72 g / min. The average drying energy is 0.14 kW with an efficiency of 88.09%, while the average exergy drying rate is 0.0014 kW with an efficiency of 72.93%.